Influence of pore structure on solute transport in degraded and undegraded fen peat soils - C. Kleimeier; F. Rezanezhad; P. Van Cappellen; B. Lennartz (Mires and Peat, 2017)
In peat soils, decomposition and degradation reduce the proportion of large pores by breaking down plant debris into smaller fragments and infilling inter-particle pore spaces. This affects water flow and solute migration which, in turn, influence reactive transport processes and biogeochemical functions. In this study we conducted flow-through reactor experiments to investigate the interplay between pore structure and solute transport in samples of undegraded and degraded peat collected in Canada and Germany, respectively. The pore size distributions and transport parameters were characterised using the breakthrough curve and two-region non-equilibrium transport model analyses for a non-reactive solute. The results of transport characterisation showed a higher fraction of immobile pores in the degraded peat with higher diffusive exchanges of solutes between the mobile and immobile pores associated with the dual-porosity structure. The rates of steady-state potential nitrate reduction were compared with pore fractions and exchange coefficients to investigate the influence of pore structure on the rates of nitrate reduction. The results indicated that the degraded peat has potential to provide the necessary boundary conditions to support nitrate removal and serves as a favourable substrate for denitrification, due to the nature of its pore structure and its lower organic carbon content compared to undegraded peat.